Transport Theory of Homogeneous Reacting Solutes - Cattani, C.; Laserra, E. (Український математичний журнал, 2001)
We consider the one-dimensional convection (advection)-dispersion equation of the transport theory of reacting solutes in porous media. A method is given for the best approximation of the numerical solution both in absence of interaction with the solid phase and in presence of discontinuous initial conditions. The class of solutions is determined by the multiresolution analysis of the partial differential operator, using Haar wavelets and splines, and it is compared with the Fourier solution. Розглядається одновимірне конвекційно-дисперсійне рівняння теорії перенесення реагуючих розчинів у пористому середовищі. Запропонований метод дає найкращу апроксимацію чисельного розв'язку як при відсутності взаємодії з твердими фазами, так і у випадку розривних початкових значень. Клас розв'язків, визначений багатовимірним розподілом змінних та при використанні функцій Хаара та сплайнів, порівнюється з розв'язками, отриманими за методом Фур'є.